ANALISIS SERANGAN CYBER MENGGUNAKAN HONEYPOT PADA WEB BERBASIS CLOUD - Bayu Setyanto Pamungkas; Irwan Sembiring (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Cloud computing has a fairly high-security system, however as it can be accessed from anywhere via the internet network, it does not rule out the possibility that the system is safe from cyberattacks, such as Port Scanning, Brute Force Attacks, Malware Attacks, and other types of cyberattacks, T-Pot Honeypot is an all in one system from Honeypot which is an additional security system to detect, trap attacks not to be able to enter the main system. Based on the research results, the implementation of this T-Pot Honeypot can detect attacks and successfully trap attackers by providing false information such as a list of open ports that are the target of the attacker's search. The log data of the detected attack results are processed by the Honeypot system and forwarded into graphs and diagrams that can be seen through the Kibana Dashboard, making it easier for administrators to monitor attack anomalies carried out by attackers so that they can be used to improve security further.